Characterizing the endometrial microbiome by analyzing the ultra-low bacteria from embryo transfer catheter tips in IVF cycles: Next generation sequencing (NGS) analysis of the 16S ribosomal gene. (March 2017) - Tao, Xin; Franasiak, Jason M.; Zhan, Yiping; Scott, Richard T.; Rajchel, Jessica; Bedard, Jenna; Newby, Robert; Scott, Richard T.; Treff, Nathan R.; Chu, Tinchun
Abstract: There is growing interest in the microbiome of the reproductive tract. The vaginal and placental microbiome has been partially characterized and shown to be related to obstetric outcomes. In this study, we developed a sensitive method to analyze 16S ribosomal RNA profiling from ultra-low bacteria counts, then studied the endometrial microbial environment by analyzing catheter tips after embryo transfers during in vitro fertilization (IVF). An extensive validation was performed on extracted DNA and culture lysates without DNA isolation from the single- or poly-microbial samples of Escherichia coli, Proteus vulgaris, Staphylococcus epidermidis, and Bacillus cereus by Illumina 16S V4 metagenomics workflows. The direct lysis method can reliably detect the genus or species taxonomic level for both single- and poly-microbial samples when there were more than 60 bacterial cells in the culture lysates. Over 99% total operational taxonomic units (OTUs) were assigned to correct genus or species. The endometrial microbiome at the time of embryo transfer was characterized by analyzing catheter tips with Illumina V4 metagenomics for 70 patients who underwent IVF cycles. Lactobacillus spp. were detected in all 70 samples. Other vaginal bacteria ( Corynebacterium, Bifidobacterium, Staphylococcus, and Streptococcus ) were also detected. The Illumina V4 metagenomics workflow with preamplification provided a rapid and sensitive method for the identification of bacterial genus or species in single- or poly-microbial samples and clinical embryo transfer specimens. Ongoing work will illuminate the relationship between endometrial microbiome and reproductive success.